Acute spatiotemporal and muscle excitation reponses to wearable lower limb loading during maximal velocity sprinting - Hurst, O.; Kilduff, L.; Johnston, M.; Cronin, J.; Bezodis, N. (ISBS Proceedings Archive (Michigan), 2018)
This study quantified the mechanical effects of adding light wearable loads to the thigh or shank segments during maximal velocity sprinting. Eight university level sprinters performed two 40 m sprints under each condition (unloaded, thigh loaded, shank loaded) in a randomised order, and effects were analysed using magnitude based inferences. In both loaded conditions, there was a possibly small decrease in step velocity which was associated with a likely small decrease in step rate and no clear difference in step length. There was a likely small increase in contact time in the thigh-loaded condition, and possibly small increases in both flight and contact time in the shank-loaded condition. There were no clear differences in biceps femoris or semitendinosus excitation between any conditions. These results provide information which can be used to objectively implement wearable resistance in to periodised training programmes.